Towards the Understanding of Damage Mechanism of Cemented Tailings Backfill - Haijun Wang (Advances in Civil Engineering)
Recent studies have shown that the damage characteristics of cemented tailings backfill (CTB) are influenced significantly by the variation of cement-tailings ratio, while the effects of other influencing factors remain unanswered. The CTB damage constitutive model, which takes the corrected coefficient of damage variable into consideration, and peak toughness are introduced to investigate the effects of fine tailings contents, curing ages, curing temperatures, and water-to-cement ratios (w/c) on the damage evolution laws, damage (DP), and specific energy (GP) at peak stress point of CTB. The results show that appropriate content of fine tailings could improve the compressive strength of CTB and reduce its damage evolution speed and DP. The damage growth rate of CTB decreases with curing age in early curing period and increases with higher curing temperature and w/c. DP of CTB takes on a descending trend with higher w/c and fine tailings content but shows an increase with curing age. There exists no significant relationship between DP and curing temperature. GP of CTB increases with curing age and higher curing temperature with a quadratic function but is on a decline with increases of fine tailings content and w/c with logarithmic and exponential function, respectively. The results obtained from our study have important application to the successful design of backfill structures in underground mines.